The relative age effect in the best track and field athletes aged 10 to 15 years old - Bezuglov, E.; Shoshorina, M.; Emanov, A.; Semenyuk, N.; Shagiakmetova, L.; Cherkashin, A.; Pirmakhanov, B.; Morgans, R. (Sports, 2022)
1) The purpose of this study was to examine the prevalence of the relative age effect (RAE) in the best young (10 to 15 years old) track and field athletes. (2) Hypothesis: The prevalence of the RAE in the best young track and field athletes of both genders will be evident in all age groups from 10 to 15 years old, which may be associated with the significant relationship between biological maturity, chronological age, and the development of physical qualities. (3) Materials and methods: In total, 1778 athletes volunteered for this study. The sample was based on the results of the best young athletes who participated in the final tournaments of the national competition "Shipovka Yunykh"("Running spikes for young athletes"), which have been held since 1981. The sample group consisted of male and female athletes classified into specific age groups: 10 to 11 years old (n = 579), 12 to 13 years old (n = 600), and 14 to 15 years old (n = 599). Analysis was performed using Jamovi 1.8.1. The Chi-square test was used to compare the RAE between different groups. (4) Results: A wide distribution of the RAE was revealed both in the general sample and in boys and girls. The percentage of "early-born" athletes was 37.6% while only 12.3% were "late-born" athletes. The difference in the severity of the RAE may reflect the small sample of athletes from the fourth quartile, which was significantly less than the sample of boys from the fourth quartile (p = 0.04, OR 1.68, 95% CI 1.02-2.78). The RAE was also evident in all age groups of boys and girls, without any statistically significant differences in the severity (p > 0.05, Chi = 2.135, V = 0.02). In the 14- to 15-year-old male athletes group, the number of early-born compared to late-born athletes peaked. The RAE was most common amongst the most successful track and field athletes. Among the competition medalists during the analyzed time period, more than 50% of athletes were born in the first quarter and no athletes were born in the fourth quarter.